Exploring the Impact of Quality of Work Life, Job Involvement, and Organizational Climate on Work-Life Balance: A Mediated Analysis Through Job Satisfaction - Syahbana, Bahtiar Nur; Hadi, Syamsul; Kirana, Kusuma Chandra (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
From an organizational point of view, work-life balance has become very important in today's working environment, and organizations have begun to consider various variables that affect well-being and employee performance. Using work satisfaction as a mediating variable, the current study investigates the relationship between WLB in an insurance broker company and QWL, job participation, and organizational climate. Quantitative data collection was performed, respecting the multi-indicators and multi-parameters nature of the variables, while the analysis was carried out using the PLSSEM software. The results indicate that WLB is significantly influenced by QWL and organizational climate, while job involvement does not show any impact. Moreover, job satisfaction, positively affected by QWL and organizational climate, does not directly influence WLB. These findings are an indication that the organization needs to prioritize enhancing QWL and fostering a positive organizational climate in most ways if it is to promote WLB and satisfaction among its employees effectively. This research found that improving the quality of work-life and organizational climate is an important factor in fostering work-life balance, especially in sector insurance brokering.